2011
DOI: 10.1586/ers.11.32
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the development of human parainfluenza virus vaccines

Abstract: In children under 5 years of age, human parainfluenza viruses (HPIVs) as a group are the second most common etiology of acute respiratory illness leading to hospitalization, surpassed only by respiratory syncytial virus but ahead of influenza viruses. Using reverse genetics systems for HPIV serotypes 1, 2 and 3 (HPIV1, 2 and 3), several live-attenuated HPIVs have been generated and evaluated as intranasal vaccines in adults and in children. Two vaccines against HPIV3 were found to be well tolerated, infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 99 publications
1
97
0
Order By: Relevance
“…Currently, there are no vaccines for RSV or HPIV, although research is underway (18,54,55). Our work could aid in timing vaccination to make optimal use of interference.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no vaccines for RSV or HPIV, although research is underway (18,54,55). Our work could aid in timing vaccination to make optimal use of interference.…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-inactivated HRSV and HPIV vaccines in the 1960s were poorly protective, and the formalin-inactivated HRSV vaccine primed for enhanced disease after subsequent HRSV infection (4,5). Parallel strategies for HRSV and HPIV vaccines have continued during the past 5 decades, and over the last 20 years, the field has largely focused on developing live attenuated vaccines delivered to the respiratory mucosa for the pediatric population (1,2,6). It is possible that prefusion F protein in its native structure may be superior to previously failed subunit vaccines (7,8), although such a vaccine might be expected, at least at first, to be best targeted to the elderly and pregnant mothers.…”
mentioning
confidence: 99%
“…In other trials, a recombinant form of the vaccine (rHPIV3cp45), re-derived from cDNA, shows a shorter passage time and reduced the risk of contamination or reversion 108 . It has been used in a phase 1 study of 40 seronegative children between 6-35 months and generates virus-specific antibodies with a tolerable safety profile 109 .…”
Section: Rsv Vaccine Developmentmentioning
confidence: 99%
“…Another trial utilizing rHPIV3cp45 in healthy young seronegative infants between 6-12 months demonstrated strong immunogenicity. These studies involved the delivery of multiple doses of vaccine with appropriate intervals which is necessary to sustain durable immune responses and children in particular are likely to benefit from the nasal route of administration due to the ability to generate protective mucosal and systemic immunity 108 .…”
Section: Rsv Vaccine Developmentmentioning
confidence: 99%